Airplanes (Blastoff! readers. 2 Mighty machines in action, ,, 2017)
"Relevant images match informative text in this introduction to airplanes. Intended for students in kindergarten through third grade"--
Takeoff! , Airplanes in action , Wings, wheels, and engines , Above and beyond.

Ships (Mighty machines in action, ,, 2017)
"Relevant images match informative text in this introduction to ships. Intended for students in kindergarten through third grade"--
Arriving at port , Ships in action , Decks, hulls, and propellers , World travelers.

How do you measure time? (A+ books. Measure it!, ,, 2011)
"Simple text and color photographs describe the units and tools used to measure time--

How do you measure weight? (A+ books. Measure it!, ,, 2011)
"Simple text and color photographs describe the units and tools used to measure weight"--

Garbage trucks (Blastoff! readers. 2 Mighty machines in action, ,, 2017)
"Relevant images match informative text in this introduction to garbage trucks. Intended for students in kindergarten through third grade"--
Trash smash , Truckloads of trash , Tires, hoppers, and blades , Cleaning up.